Eksplorasi Desain Karakter untuk Buku Cerita Pop-Up “Pixel dan Pixie yang Cerewet” - Oscar Ade Gunawan; Mahimma Romadhona; Sri Wulandari (LPPM Universitas Bhinneka Nusantara, 2026)
The development of digital technology has made gadget use inseparable from daily life, including among children. The use of gadgets among children without proper understanding and supervision can lead to addiction, increased stress levels, reduced physical activity, emotional distress, and behavioral problems. Therefore, efforts are needed to educate children about the dangers and impacts of excessive gadget use. One of the efforts that can be carried out is the use of educational media that can convey messages to children optimally. In this study, the effectiveness of the media is assessed based on its ability to increase children's visual interest, facilitate understanding of the story content, and help children recognize characters and the messages conveyed. One medium that has this potential is a pop-up storybook. In the creation of a pop-up book, the process of character design cannot be separated. This study aims to explore the process of character design development through the stages of the design thinking method, which include concept formulation, the creation of alternative designs, and testing of visual preferences in a pop-up storybook. This research is part of a final project on designing a pop-up storybook as an educational medium for children's gadget use, entitled